Effect of Ozone Treatment Intensity on Pasting Property, Protein Composition, and Steamed Bread Quality of Ozone-Treated Wheat Flour. (23rd August 2022) - Zhang, Wei; Wang, Haoxuan; Li, Liuyan; Zeng, Xuefeng; Shu, Zaixi; Wang, Pingping
Abstract : Wheat flours were treated with ozone gas at low- and high-intensity conditions (0.61 and 3.82 g/h) for different durations (short: 5 min; long: 30 min), and the ozone-treated flours were evaluated in quality properties, including pH, protein component, water molecular mobility of dough, pasting property, and steamed bread quality. At both conditions, ozone treatment decreased the pH of wheat flour. Long duration of high-intensity treatment aroused significant increase in insoluble polymeric protein (IPP) content of wheat flour, but other treatments did not significantly change the IPP content. Dough of ozone-treated flour had higher water molecular mobility than that of native flour. Short duration of low-intensity treatment did not significantly change most pasting viscosity parameters of wheat flour, but other treatments increased the peak viscosity, breakdown viscosity, and setback viscosity. Steamed bread of ozone-treated flour had lower specific volume and pore uniformity than that of native flour. Long duration of high-intensity treatment of flour increased the hardness and chewiness of the steamed bread product, but other treatment showed opposite effect. Among the four ozone treatments, long duration of high-intensity treatment aroused the greatest change in pH, IPP, water molecular mobility of dough, and the quality of steamed bread, while short duration of low-intensity treatment had the minimum effect. Long duration of low-intensity treatment was close to the short duration of high-intensity treatment in quality attributes of wheat flour and the total ozone yield. These results suggested that the quality of wheat flour gradually changed with the increase of total ozone yield, and overozonization would greatly deteriorate the quality of wheat flour.